Anatomical relationships between medullary veins and three types of deep-seated malignant brain tumors as detected by susceptibility-weighted imaging. Issue 2 (February 2020) - Yang, Shih-Hung; Hong, Chien-Tai; Tsai, Fong Y.; Chen, Wei-Yu; Chen, Chia-Yuen; Chan, Wing P.
Abstract : Background: Deep-seated brain tumors can be difficult to differentiate. Three tumor types (primary central nervous system lymphoma [PCNSL], high-grade glioma, and metastatic brain tumors), identified by susceptibility-weighted imaging, have different relationships with small medullary veins, and these relationships can be used to enhance diagnostic accuracy. Methods: Records of patients with pathology confirmed malignant brain tumors who received susceptibility-weighted imaging between 2009 and 2015 were reviewed. A total of 29 patients with deep-seated malignant brain tumors in the territory of small medullary veins were enrolled in this study. The sensitivity, specificity, and diagnostic accuracy of medullary vein blockage (MVB), defined as a small medullary vein terminating at the margin of the tumor, for indicating malignant brain tumors were analyzed. Results: Of 11 patients with PCNSLs, 5 with high-grade gliomas, and 13 with metastases, only the latter presented MVBs. The sensitivity, specificity, and accuracy of using MVBs for diagnosing metastatic tumors were 76.9%, 100%, and 89.7%, respectively. Conclusion: An MVB is an accurate sign for differentiating metastatic brain tumors from two other common malignancies and thus provides a useful tool for preoperative planning.